Seed migration after transperineal interstitial prostate brachytherapy by using loose seeds: Japanese prostate cancer outcome study of permanent iodine-125 seed implantation (J-POPS) multi-institutional cohort study - Nakano, Masahiro (Radiat Oncol, 2015)
BACKGROUND: The incidence and associated factors of loose seed migration were investigated in cohort 1 of the Japanese Prostate Cancer Outcome Study of Permanent Iodine-125 Seed Implantation (J-POPS). METHODS: The study subjects were 2160 patients, consisting of 1641 patients who underwent permanent iodine-125 seed implantation (PI) and 519 patients who underwent PI combined with external beam radiation therapy (PI + EBRT). The presence or absence of seed migration to the chest and abdominal/pelvic region was determined. RESULTS: Seed migration was observed in 22.7 % of PI group patients and 18.1 % of PI + EBRT group patients (p = 0.0276). Migration to the lungs and abdominal/pelvic region was observed in 14.6 % and 11.1 % of the patients in the PI group, and 11.2 % and 8.5 % of the patients in the PI + EBRT group, respectively. In the PI group, the number of implanted seeds was associated with the seed migration incidence. Neither the PI nor the PI + EBRT group showed any difference in the volume of the prostate receiving 100 % of the prescribed dose (V100 [%]) or the minimal dose received by 90 % of the prostate volume (D90 [Gy]) between the patients with and without seed migration. CONCLUSIONS: This prospective cohort study investigating the largest number of past cases showed no difference in D90 (Gy) or V100 (%) between seed migration or the absence thereof in both the PI group and PI + EBRT group. TRIAL REGISTRATION: ClinicalTrials.gov: NCT00534196